Communication Strategy Based on Islam Value of U-Jek Online Taxibike (Ojek) in Semarang - Mubarok, Mubarok (Universitas Semarang, 2018)
U-Jek was developed by Zarkasyi, in Unissula Semarang. This study aims to explain the communication strategy to develop an online taxibike (ojek) value-based Islam. This research strategy is descriptive qualitative research. Through this strategy, researchers want to know the current condition of U-Jek, ojek in Semarang. Researchers will explain the development of student ojek in Semarang, researchers also eager to analyze the using of communication strategy, and to formulate the right strategy to develop student ojek in Semarang. The researcher also elaborates U-Jek's communication strategy and reveals its advantages and disadvantages. The results show that the biggest challenge of U-Jek communication strategy is the commitment of its managers. U-Jek Manager must increase its communication channel capacity by developing digital application service. In the pyramid communication plan, U-Jek's manager does not pay attention to the aspect of the framework of issues which become message base.